2003
DOI: 10.1093/jac/dkg366
|View full text |Cite
|
Sign up to set email alerts
|

Mastic gum has no effect on Helicobacter pylori load in vivo

Abstract: Despite reported anti-H. pylori action in vitro, this preliminary study shows that mastic has no effect on H. pylori in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 8 publications
0
28
0
2
Order By: Relevance
“…Mastic has also been reported to possess antioxidant [12] and antibacterial [13] activity. With reference to gastrointestinal disorders, the effectiveness of the resin against peptic ulcers is evident [14] in most studies, while only in two reports there is no effect on H pylori eradication in vivo [15,16] . Furthermore, regarding gastric mucosa, the plant has been shown to be hepatoprotective in tetrachloride-intoxicated rats [17] and to suppress the extent of iron-induced lipid peroxidation in rat liver homogenates [18] , without any toxic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Mastic has also been reported to possess antioxidant [12] and antibacterial [13] activity. With reference to gastrointestinal disorders, the effectiveness of the resin against peptic ulcers is evident [14] in most studies, while only in two reports there is no effect on H pylori eradication in vivo [15,16] . Furthermore, regarding gastric mucosa, the plant has been shown to be hepatoprotective in tetrachloride-intoxicated rats [17] and to suppress the extent of iron-induced lipid peroxidation in rat liver homogenates [18] , without any toxic effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a more recent in vivo study of H. pylori infection, the activity of mastic gum was compared with antibiotic eradication schemes, and after a 7-day therapy no eradication of the bacterium from the stomachs of mice receiving mastic was observed (17). Finally, H. pylori-positive patients were treated with mastic capsules for 7 days, and they all remained H. pylori positive after the administration (6). The last two studies concluded that no "antibiotic-like" activity should be expected from crude mastic.…”
mentioning
confidence: 99%
“…Most Chios mastic doses previously reported in human studies were around this level, e.g. 5 g/day/person (Triantafyllou et al, 2007), 4 g/day/person (Bebb et al,2003), 2.2 g/day/parson (Kaliora et al, 2007a(Kaliora et al, , 2007b, or 1 g/day/person (Al-Habbal et al, 1984). Favorable effects of mastic such as anticarcinogenic potential could be achieved at relatively low doses without any toxicity (He et al, 2006).…”
Section: Chios Mastic (Pistacia Lentiscus L) and Cancer Chemopreventionmentioning
confidence: 96%